2018
DOI: 10.1093/mnras/sty1920
|View full text |Cite
|
Sign up to set email alerts
|

The extended HeIIλ4686 emission in the extremely metal-poor galaxy SBS 0335-052E seen with MUSE★

Abstract: SBS 0335-052E, one of the most metal-poor (Z ∼ 3-4% Z ⊙ ) HeII-emitter starbursts known in the nearby universe, is studied using optical VLT/MUSE spectroscopic and Chandra X-ray observations. We spatially resolved the spectral map of the nebular HeIIλ4686 emission from which we derived for the first time the total HeII-ionizing energy budget of SBS 0335-052E. The nebular HeII line is indicative of a quite hard ionizing spectrum with photon energies > 4 Ryd, and is observed to be more common at high-z than loca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 108 publications
2
61
0
Order By: Relevance
“…It is also one of most well-studied. Although it is farther and more metal-rich than the prototypical, I Zw 18, which is located at ∼18.2 Mpc (Aloisi et al 2007) and whose North-Western component has 12+log(O/H)=7.17 ± 0.04 (Skillman & Kennicutt 1993), the integrated He luminosity of SBS 0335-052E (1.87e39 erg s −1 , Kehrig et al 2018) is larger than that of I Zw 18 (1.12e38 s −1 , Kehrig et al 2015). This makes of SBS 0335-052E a unique target to test spectral synthesis models.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…It is also one of most well-studied. Although it is farther and more metal-rich than the prototypical, I Zw 18, which is located at ∼18.2 Mpc (Aloisi et al 2007) and whose North-Western component has 12+log(O/H)=7.17 ± 0.04 (Skillman & Kennicutt 1993), the integrated He luminosity of SBS 0335-052E (1.87e39 erg s −1 , Kehrig et al 2018) is larger than that of I Zw 18 (1.12e38 s −1 , Kehrig et al 2015). This makes of SBS 0335-052E a unique target to test spectral synthesis models.…”
Section: Introductionmentioning
confidence: 91%
“…As described in , to correct for this, the resulting output sky-spectra from the DRS were first modified by interpolation over the affected wavelengths and subsequently fed into a second iteration of muse_scipost, as input sky-spectra. The uncorrected MUSE datacube was exploited by Kehrig et al (2018) to show that the total He flux of the galaxy, including regions outside of our aperture, can only be produced by either single, rotating metal-free stars or a binary population with Z∼10 −5 and a "top-heavy" IMF.…”
Section: Muse Spectroscopymentioning
confidence: 99%
“…Previous observations have revealed that many low-metallicity star-forming galaxies produce these hard photons much more efficiently than predicted by stellar population synthesis models (e.g. Shirazi & Brinchmann 2012;Senchyna et al 2017;Berg et al 2018;Kehrig et al 2018) which suggests significant systematic uncertainties may arise in the interpretation of He ii emission at high redshift. In particular, we found in S17 that the relative flux beyond the He + -ionizing edge is strongly dependent on metallicity, and suggests a dramatic upturn in the hardness of this ionizing radiation at low metallicities.…”
Section: He II Emission In the Xmp Regimementioning
confidence: 99%
“…All line fluxes in Figs 6 and 7 are corrected for attenuation by dust, as prescribed in the original studies. We note that the line ratios in these figures are subject to uncertainties linked to the different apertures used to observe different galaxy samples, as highand low-ionization lines are not necessarily co-spatial (see, e.g., Kehrig et al 2018).…”
Section: Global Observational Properties Of the Full Samplementioning
confidence: 99%